ШАХС ФОЖИАСИ ТАЛҚИНИДА БЕГОНАЛАШУВ МАСАЛАСИ - Хамракулова, Х. (SCIENCE and SOCIETY, 2020)
This article deals with the concept of isolation out in interpretation of individuals tragedy. There by, it is found that losing position in society may lead to tragedy and also one of the main key of creating masterpiece of out. The article focuses on self-alienation concept of individuals, so that society transforms them as thinkers, and sometimes it evokes to think in tragedic scale.
Keywords: human mind; cognitive evolution; life and death problem; personality tragedy; existential literature; alienation in literature